Meta-Analysis of the Effect of Heavy Lifting on Low Back Pain Among Health Workers - Khairunnisa; Tamtomo, Didik Gunawan; Murti, Bhisma (Indonesian Journal of Medicine, 2024)
Background: Low back pain is common in healthcare workers including doctors, nurses, midwives and physiotherapists, due to the nature of their work. These healthcare workers are often involved in tasks that involve heavy lifting. Manual patient handling, and awkward postures that are an integral part of care may have an effect on musculoskeletal injuries. This study aims to analyze the effect of heavy lifting on low back pain among healthcare workers. Subjects and Method: This study is a systematic review and meta-analysis study. The search for articles was carried out in accordance with the PICO Model eligibility criteria which include: P = Health workers, I = Heavy lifting, C = No heavy lifting, O = Low back pain. The articles used came from 2 databases, namely: PubMed and Science Direct. The keywords used were "heavy lifting" AND "low back pain" OR "musculoskeletal of low back pain” AND "healthcare professional" OR "healthcare workers". The inclusion criteria in this study included full-text articles with a cross-sectional study design, the relationship measure used was the adjusted Odds Ratio (aOR), articles published in the range 2014-2022, and the outcome was Low back pain. Articles were analyzed using the PRISMA diagram and the Review Manager 5.4.1 application. Results: 9 articles from Ethiopia, Japan, Malaysia, Nigeria, Pakistan, Saudi Arabia and Uganda. Healthcare workers who performed heavy lifting increased lower back pain by 4.36 times compared to those who did not, and the results were statistically significant (aOR=4.36; 95% CI=3.07 to 6.20; p<0.001). Conclusion: A meta-analysis of 9 cross-sectional studies concluded that heavy lifting increases low back pain in healthcare workers.